Distribution. Cool temperate waters of the N Pacific, primarily between 38° N and 47° N, including the Yellow Sea, Sea ofJapan, S Sea of Okhotsk, S Bering Sea, and S Gulf of California. in Delphinidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Distribution. Cool temperate waters of the N Pacific, primarily between 38° N and 47° N, including the Yellow Sea, Sea ofJapan, S Sea of Okhotsk, S Bering Sea, and S Gulf of California. Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Delphinidae, pp. 410-526 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 491, DOI: 10.5281/zenodo.6610922